Analisis Penerapan Pasal 41 Undang-Undang Nomor 1 Tahun 1974 Tentang Hak Nafkah Anak (Study Kasus Putusan Hakim Pengadilan Agama Lubuklinggau Nomor: 371/Pdt.G/2021/Pa.LLg) - Fitrian, Fitrian; Kisworo, Budi; Warlizasusi, Jumira (STAI Bumi Silampari, 2022)
Marriage is a legal bond to build a happy home and family where husband and wife carry the trust and responsibility. There is a divorce in the household, so for both parents who have separated the responsibility for their children remains. In this study, the author uses a normative legal approach. This means that what is produced is in accordance with the theory, namely an approach to the problem by studying and analyzing an applicable statutory regulation to be used as a basis for solving problems that occur in society. This study finds that there are still problems in the practice of marriage in the dynamics of law in Indonesia, both regarding divorce issues and those relating to the compilation of existing laws